Evaluation of technological parameters of convective drying of pumpkin seeds with vibro-ozonation intensification of the process - I. Palamarchuk; M. Mushtruk; N. Mushtruk (Тваринництво та технології харчових продуктів, 2025)
Thermal and mechanical effects commonly pose challenges during the heat and mass transfer treatment of seed products. Consequently, drying methods utilising a vibratory fluidised bed, which minimise these effects on plant-based products, remain relevant. This study aimed to enhance the driving force and, consequently, the efficiency of the dehumidification process for thermolabile plant raw materials by employing vibro-mechanical activation of seed material movement, increasing electro-osmotic pressure to improve moisture diffusion conditions, and achieving disinfection during processing. The research methodology included experimental investigations conducted using a vibratory bed system with an ozone-air drying agent. The study examined the influence of vibration frequency, ozone concentration, and temperature regime on drying kinetics, heat and mass transfer rates, disinfection levels, and energy efficiency. Based on the results, a process flow diagram for convective drying of grain and cereal materials was developed, incorporating vibratory and ozonising means to intensify the process. The proposed process flow diagram ensured the necessary disinfection of the product, improved heat transfer conditions, maintained consistent hydraulic resistance along the entire rarefaction chamber, and ensured uniform drying. It also reduced energy consumption, enhanced the durability, reliability, and productivity of the process, and prevented overheating of the material, thereby enabling the drying of thermolabile products. Research findings demonstrated that filtration drying with vibroozonation reduced the processing time for pumpkin seeds by a factor of 1.67 and decreased energy consumption by a factor of 1.71 compared to conventional convective methods. The highest drying rate was achieved with filtration vibratory drying, which proved to be 1.68 times more efficient than convective drying. The practical significance of this research lies in the development of drying equipment that ensures uniform drying, mitigates the risk of overheating, and improves the longevity and productivity of the process. The obtained results can be implemented in industrial settings for the efficient processing of thermolabile agricultural products